HISTORICAL SOURCE STUDIES OF THE SCIENTIFIC HERITAGE OF ULUGBEK’S ACADEMY EDUCATION PROVIDERS (British Journal of Global Ecology and Sustainable Development, 2023)
Maulana Alauddin Ali ibn Muhammad Kushchi Samarkhandi (1403-1474) was an astronomer and mathematician, one of the famous representatives of Ulugbek's scientific school, his closest student. Ali Kushchi had a significant impact on the development of mathematics in the countries of the Near and Middle East in the 16th and 17th centuries. The work "Hisob risola" was used as a textbook in the madrasah of Central Asia. In this work, Indian arithmetic (decimal system), astronomical arithmetic (hexadecimal system) and geom. (handasa) talk about new ideas. In "Kitab ul-Muhammadiya" Ali Qushchi shows methods for deriving arbitrary natural roots from numbers and Newton's binomial formula, his methods are similar to the method currently known as the Ruffini-Horner scheme. In this work, Ali Kushchi gives formulas for the approximate calculation of the square root and the root of the first degree in general. It should be noted that the current designation of the root in the works of Turkestan scientists was not used: the root was written in words.